iFingerstyle: Development of a Mobile Application to Generate Fingerstyle Tablature - Syamsuddin, Syafiq; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2023)
“iFingerstyle” is the guitar mobile application that implementing the simple User Interface (UI) and User Experience (UX), including audio recognition technology that can generate fingerstyle tablature, because the existing similar application has inexplicit instructions, and not implement the fingerstyle tablature generator feature. Next, the main research objective is to develop a mobile-based guitar application that provide audio recognition feature, while targeted users are the people who fascinated to learn about the basic of guitar. Furthermore, the methodology applied for this project is Evolutionary Prototyping model, which all the requirements are identified through survey after the planning phase and has the iteration process in the development phase that depends on the testing evaluation. In addition, the project is expected to finish successfully and all the requirements can be fulfilled according to the analysis. Thus, “iFingerstyle” will satisfy the target user and refer for the incoming project with similar domain.